PERAN PENDIDIK DALAM MENANAMKAN NILAI AGAMA DAN MORAL ANAK USIA DINI - Aulia Laily Rizqina; Bayu Suratman (Didaktika : Jurnal Kependidikan, 2020)
This study aims to describe the role of educators in internalizing religious and moral values to early chidhood. This study used a qualitative descriptive method based on observations, interviews, and documentation at Al-Hikmah IT Kindergarten Semarang. The results of this study indicate that the most dominant educators’ role in instilling religious and moral values to students is the role of educators as models. While the most dominant method of inculcating religious and moral values applied is the habituation method.  The typical method of inculcating religious and moral values in Al-Hikmah IT Kindergarten Semarang is through storytelling method using books called pillars. The book contains the character values that are in accorcance with the content standards regarding the level of achievement of children development in the scope of development of religious and moral values.        Keywords: educators, religious and moral values, early chilhood